A Sociolinguistic Look at Intrusive r - Agustín Lana, Rodrigo (Journal of Artistic Creation and Literary Research, 2025)
This paper will look at the use of intrusive r in different varieties of English across the English-speaking world. The main purpose of the paper will be to examine how native speakers of English use intrusive r and how this usage correlates with sociolinguistic factors like social class, age, gender and level of education. With this aim in mind, a range of empirical studies conducted from the 1970s onwards has been selected to illustrate the analysis. The discussion of the results of these studies has confirmed two of the ideas we had before we embarked on writing this paper. First, that varieties of English worldwide are shifting towards greater rhoticity, and second, that not only does a negative correlation between the occurrence of intrusion and socioeconomic status exist, but that speakers who pronounce intrusive r are also the target of social stigmatization.